INCREASING YOUTH KNOWLEDGE IN HANDLING SYNCOPE CASES IN STUDENTS OF THE SENIOR HIGH SCHOOL OF MUHAMMADIYAH 3 SIDOARJO, TULANGAN SUB-DISTRICT, SIDOARJO DISTRICT - Dini Prastyo Wijayanti; Kusuma Wijaya Ridi Putra; Apriliyani Ayu Lestyaningsih; Sekar Mega Oktavino; Shelly Mujidah; Anju Andayani; Sisilia Ayu Titania Tangkelajuk; Sherly Ayunda (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
First Aid Health Promotion Activities in syncope cases at the Senior High School of Muhammadiyah 3 Sidoarjo, Tulangan Sub-District, Sidoarjo District is a form of education in the form of counseling aimed at increasing adolescent knowledge about first aid methods when encountering syncope cases. The activity was held on November 15, 2018 at the Senior High School of Muhammadiyah 3 Sidoarjo, Tulangan Sub-District, Sidoarjo District. With the goal is students of the Senior High School of Muhammadiyah 3 Sidoarjo, Tulangan Sub-District, Sidoarjo District. Before the implementation of the activity, there is a process of preparing activities for 3 weeks before the activities are carried out, starting from the selection of health counseling materials to the submission of permits to related parties. As an evaluation, the activity was attended by 35 students and 1 teacher as participants participating in the activity with enthusiasm and conduciveness, activities can be carried out on time smoothly. Keywords: Syncope, first aid health promotion, adolescent’s knowledge.